2018
DOI: 10.18632/oncotarget.25156
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose-escalation study of F50067, a humanized anti-CXCR4 monoclonal antibody alone and in combination with lenalidomide and low-dose dexamethasone, in relapsed or refractory multiple myeloma

Abstract: PurposeMultiple myeloma (MM) remains an incurable disease as tumor cells ultimately resist to all available drugs. Homing of tumor cells to the bone marrow microenvironment, involving especially the CXCR4/SDF-1 axis, allows them to survive, proliferate and resist to therapy. F50067, a humanized anti-CXCR4 IgG1 antibody, has promising preclinical activity in MM.We present a phase I multicenter escalation study in relapsed/refractory MM (RRMM) to determine the maximum tolerated dose (MTD) for F50067 alone and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Fouquet et al studied 14 RRMM patients as F50067 monotherapy and combination of F50067 + Rd (low-dose dexamethasone) with 66.7% ORR (≥PR) in combination cohort and OR of 33.3% (≥SD). Investigators discontinued the study due to hematological toxicities [48].…”
Section: Resultsmentioning
confidence: 99%
“…Fouquet et al studied 14 RRMM patients as F50067 monotherapy and combination of F50067 + Rd (low-dose dexamethasone) with 66.7% ORR (≥PR) in combination cohort and OR of 33.3% (≥SD). Investigators discontinued the study due to hematological toxicities [48].…”
Section: Resultsmentioning
confidence: 99%
“…F50067 is a humanized monoclonal IgG1 anti-CXCR4 antibody and exerts antitumor effects via reducing the interaction of MM cells with the BM microenvironment and inducing antibody-dependent cellular cytotoxicity and compliment-dependent cytotoxicity. Fouquet et al reported a phase I dose escalation study of F50067 alone and in combination with lenalidomide and low-dose dexamethasone (Len-dex) in RRMM [104]. Moreover, 14 patients with RRMM were enrolled in the study.…”
Section: F50067mentioning
confidence: 99%
“…The analysis excludes targets that would require CNS penetration for efficacy unless the program harnesses BBB transcytosis technology, where binding to the transferrin receptor (TfR) is used for delivery into the brain and can be engineered as a bispecific antibody or into the Fc domain of the molecule. Anti-GPCR antibodies are also under investigation as combination therapies, for example, with checkpoint inhibitor antibodies [51] or lenalidomide and dexamethasone [52] or in combination with cell therapy [53]. What is also apparent is the significant interest and sustained activity in directing mAbs to this important drug class as evidenced by the total number of programs in the R&D pipeline and the success of more mAbs attaining advanced clinical development over the past decade (Figure 3).…”
Section: Progress In the Global Gpcr-antibody Randd Pipelinementioning
confidence: 99%